Step 1: Given,

The equations 5x−2y−4z=3 and 3x+3y+2z=−3. We have to eliminate z from equation 1 and 2.

Step 2: Calculation

5x-2y-4z=3...(1)

3x+3y+2z=-3...(2)

Mult.(2)by 2, add(1)+(2),we get

5x-2y-4z=3

6x+6y+4z=-6

We get the equation

\(\displaystyle\Rightarrow{11}{x}+{4}{y}=-{3}\)

The equations 5x−2y−4z=3 and 3x+3y+2z=−3. We have to eliminate z from equation 1 and 2.

Step 2: Calculation

5x-2y-4z=3...(1)

3x+3y+2z=-3...(2)

Mult.(2)by 2, add(1)+(2),we get

5x-2y-4z=3

6x+6y+4z=-6

We get the equation

\(\displaystyle\Rightarrow{11}{x}+{4}{y}=-{3}\)